THE EFFECT OF CASH FLOW VOLATILITY AND EARNINGS PERSISTENCE ON CUMULATIVE ABNORMAL RETURN (CAR) OF FIRMS WITHIN THE FOOD AND BEVERAGES SUB-SECTOR LISTED ON THE INDONESIAN STOCK EXCHANGE - Grasela Trinita Tawalujan; Kenneth August Sahetapy (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study investigates the effect of cash flow volatility and earnings persistence on cumulative abnormal return (CAR) in manufacturing firms within the food and beverages sub-sector listed on the Indonesia Stock Exchange during the 2019–2022 period. Grounded in signalling theory and the efficient market hypothesis, this research employs a causal research design using secondary data obtained from publicly available financial statements and stock market information. A purposive sampling method was applied, resulting in 27 firm-year observations that met the predetermined criteria. Cash flow volatility is measured using the standard deviation of operating cash flows relative to total assets, while earnings persistence is estimated through a regression model of current earnings on prior-period earnings. CAR is calculated based on abnormal returns accumulated over a one-week window following financial statement announcements. The empirical analysis is conducted using multiple linear regression after satisfying classical assumption tests. The findings reveal that cash flow volatility does not have a significant effect on CAR, indicating that investors do not strongly react to fluctuations in operating cash flows. In contrast, earnings persistence has a positive and significant effect on CAR, suggesting that the market responds favourably to firms with stable and sustainable earnings. These results imply that earnings quality, as reflected by persistence, is more relevant than cash flow volatility in influencing market reactions within the Indonesian food and beverages sub-sector.